Exploring teachers’ views and roles on the integration of artificial intelligence in modern education - Jeffry M. Saro; Janet T. Banguis; Maria Liza T. Escarda; Zenmar L. Gendive-Latore; Analiza M. Sodio; Cherry Pinky P. Mulato (University of Muhammadiyah Malang, 2026)
Background: The rapid advancement of Artificial Intelligence (AI) is transforming modern education, influencing instructional design, assessment practices, and administrative tasks. However, teachers’ readiness and lived experiences in integrating AI remain insufficiently explored, particularly within the Division of Agusan del Sur. Objectives: This study aimed to explore teachers’ perceptions, evolving roles, and challenges in integrating AI into classroom instruction and educational practice. Methods: A qualitative phenomenological research design was employed. Using purposive sampling, fifteen teachers participated in individual interviews and focus group discussions. Data were analyzed through thematic analysis using hand coding to identify recurring patterns and essential meanings from participants lived experiences. Results: Four major themes emerged regarding teachers’ perceptions: understanding of AI in education, concerns about AI integration, positive impacts on teaching and learning, and future outlook on AI. Teachers recognized AI’s potential for personalized learning and task automation but expressed concerns about job displacement, ethical issues, and data privacy risks. Additional findings revealed evolving roles as instructional designers, digital mentors, and lifelong learners. Key challenges included limited professional training, technological constraints, curriculum misalignment, and resistance to change. Conclusion: Strengthening professional development, clarifying pedagogical roles, and establishing supportive policies are essential to ensure meaningful and sustainable AI integration in education.